Pengaruh Beban Kerja dan Stres Kerja terhadap Produktivitas Karyawan pada PT Catur Mitra Sejati Sentosa - Dewi Kartika Saragih; Elmira Siska (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study was conducted at PT Catur Mitra Sejati Sentosa, where high work pressure was observed due to daily production or sales targets that must be achieved within 8 working hours. Employees who fail to meet these targets are not allowed to leave on time, leading to increased workload and work stress. This condition is suspected to significantly affect employee productivity. The aim of this research is to examine the influence of workload and work stress on employee productivity, both partially and simultaneously. The research uses a quantitative approach with a survey method by distributing questionnaires to 51 respondents. Data analysis was carried out using SPSS version 26 through validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests. The findings of the study indicate that workload has a significant effect on employee productivity, as does work stress. Both workload and work stress are positively correlated with lower productivity levels. Moreover, when assessed together, both variables also simultaneously influence productivity significantly. This suggests that the company’s high work pressure, driven by unmet targets, contributes directly to reduced work efficiency and increased stress. Therefore, the company needs to manage workload and work stress effectively, ensuring that work expectations are realistic and that employees are given adequate support to meet these expectations. Optimizing these factors can enhance employee productivity, reduce stress, and improve overall company performance.